An Attempt to Apply Canonical Analysis to Investigate the Dependencies between the Level of Organic Farming Development in Poland and the Chosen Environmental Determinants - Joanna Smoluk-Sikorska; Mariusz Malinowski (Energies, 2021)
Polish organic agriculture has faced rapid growth in the recent two decades. Nevertheless, one may observe considerable discrepancies in organic agriculture development in specific regions of Poland. Therefore, it is necessary to recognize the key conditions for this development and its spatial differentiation. Since the relationship between organic farming and the natural environment has a fundamental meaning in this production system, it is crucial to study the development determinants of environmental characters. Thus the paper aims to identify the level of organic farming development in Polish districts and to investigate multidimensional relations between this level and selected environmental conditions. In order to identify the range and direction of those multidimensional relations between the discussed phenomena, canonical analysis was applied. Within the conducted study, proprietary synthetic measures were constructed (using the TOPSIS—Technique for Order of Preference by Similarity to Ideal Solution), and linear ordering of the objects described by a large number of variables was employed. To define the strength and direction of the dependencies among constructed synthetic indices of the level of organic farming development and environmental conditions, a correlation analysis was performed. All 380 districts in Poland were considered as the investigated objects. Based on the variables describing selected environmental conditions, one may explain nearly 26.7% of the variance of variables related to organic agriculture development.